The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.ophtha.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Esotropia and Exotropia Preferred Practice Pattern®

Abstract: for Quality Eye Care without any external financial support. Authors and reviewers of the guidelines are volunteers and do not receive any financial compensation for their contributions to the documents. The guidelines are externally reviewed by experts and stakeholders before publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 200 publications
0
36
0
1
Order By: Relevance
“…Twenty‐eight patients with XT between 14 to 40 years of age, and 27 age‐ and sex‐ matched healthy controls were recruited from 1 March 2019 to 30 June 2019. Inclusion criteria were 1) intermittent or constant XT, 21 with exodeviation angles between 15 Δ and 80 Δ ; 2) no history of strabismus surgery; 3) coexisting vertical deviation ≤ 5 Δ . Exclusion criteria were (1) amblyopia (i.e., an interocular difference in visual acuity of less than 0.2 logMAR and best‐corrected visual acuity of 0.1 logMAR or worse, in one or both eyes); (2) anisometropia greater than 2.50D; (3) high myopia or hyperopia > 6.00D spherical equivalent; (4) incomitant or acquired strabismus; (5) neurological disorders or psychiatric diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐eight patients with XT between 14 to 40 years of age, and 27 age‐ and sex‐ matched healthy controls were recruited from 1 March 2019 to 30 June 2019. Inclusion criteria were 1) intermittent or constant XT, 21 with exodeviation angles between 15 Δ and 80 Δ ; 2) no history of strabismus surgery; 3) coexisting vertical deviation ≤ 5 Δ . Exclusion criteria were (1) amblyopia (i.e., an interocular difference in visual acuity of less than 0.2 logMAR and best‐corrected visual acuity of 0.1 logMAR or worse, in one or both eyes); (2) anisometropia greater than 2.50D; (3) high myopia or hyperopia > 6.00D spherical equivalent; (4) incomitant or acquired strabismus; (5) neurological disorders or psychiatric diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Depending upon the clinic-etiological features, primary exotropia was classified into basic non-specific type (exotropia approximately equal for near and distance), convergence insufficiency type (exotropia greater for near than distance, ≥10 prism diopters [PD]), and divergence excess (exotropia greater for distance than near, ≥10 PD). Esotropia was classified into accommodative esotropia (due to overaction of convergence associated with accommodation reflex) and non-accommodative esotropia (all those primary esodeviations in which the amount of deviation is not affected by the state of accommodation and roughly equal in amount at distance and near fixation) [14].…”
Section: Diseases Definition and Classificationmentioning
confidence: 99%
“… 6 Early detection and prompt management of strabismus in children is vital as it can improve their long-term visual and sensorimotor outcomes. 7 It has been reported that strabismus is the most common cause of childhood amblyopia. 8 , 9 Children with apparent strabismus may also be subject to psychosocial sequelae, such as lower self-confidence and self-esteem anxiety.…”
Section: Introductionmentioning
confidence: 99%